Jasmonates induce Arabidopsis bioactivities selectively inhibiting the growth of breast cancer cells through CDC6 and mTOR. Issue 4 (19th November 2020) - Bömer, Moritz; Pérez‐Salamó, Imma; Florance, Hannah V.; Salmon, Deborah; Dudenhoffer, Jan‐Hendrik; Finch, Paul; Cinar, Aycan; Smirnoff, Nicholas; Harvey, Amanda; Devoto, Alessandra
Summary: Phytochemicals are used often in vitro and in vivo in cancer research. The plant hormones jasmonates (JAs) control the synthesis of specialized metabolites through complex regulatory networks. JAs possess selective cytotoxicity in mixed populations of cancer and normal cells. Here, direct incubation of leaf explants from the non‐medicinal plant Arabidopsis thaliana with human breast cancer cells, selectively suppresses cancer cell growth. High‐throughput LC‐MS identified Arabidopsis metabolites. Protein and transcript levels of cell cycle regulators were examined in breast cancer cells. A synergistic effect by methyljasmonate (MeJA) and by compounds upregulated in the metabolome of MeJA‐treated Arabidopsis leaves, on the breast cancer cell cycle, is associated with Cell Division Cycle 6 (CDC6), Cyclin‐dependent kinase 2 (CDK2), Cyclins D1 and D3, indicating that key cell cycle components mediate cell viability reduction. Bioactives such as indoles, quinolines and cis‐(+)‐12‐oxophytodienoic acid, in synergy, could act as anticancer compounds. Our work suggests a universal role for MeJA‐treatment of Arabidopsis in altering the DNA replication regulator CDC6, supporting conservation, across kingdoms, of cell cycle regulation, through the crosstalk between the mechanistic target of rapamycin, mTOR and JAs. This study has important implications for the identification of metabolites with anti‐cancer bioactivities in plants with no known medicinal pedigree and it will have applications in developing disease treatments